Implementation of Sludge-Filled Geotextile Tubes as a Sustainable Coastal Protection Measure in Muddy Coastline - Nastiti Tiasundari; Dandung Sri Harninto; Rizal Ansari Ady; Dede M. Sulaiman (Indonesian Geotechnical Journal, 2026)
Coastal erosion is one of the major challenges faced along the northern shoreline of Java Island. This phenomenon results in degradation of the coastline, threatening not only the local ecosystems but also the livelihoods of coastal communities. The soft, muddy coastal characteristics of this region make conventional hard-engineering structures less effective and unsustainable, prompting the need for alternate solutions. This study aims to evaluate the effectiveness of sludge-filled geotextile tubes (GI-Tubes) as an erosion control measure in muddy coastal areas. A field experiment was conducted using three GI-Tube units, each measuring 1.3 meters in height and 20 meters in length, installed parallel to the shoreline. The GI-Tubes were made from double-layered needle-punched staple fiber polypropylene non-woven geotextile and filled with locally sourced sludge mixed with flocculants to promote effective sediment floc formation within the tubes. The small opening size of the non-woven geotextile facilitated efficient dewatering while retaining the sludge inside. The outer layer of the GI-Tube provided high UV resistance and enhanced sediment-trapping capability, offering additional protection and extended durability. The double-layered design of the geotextile tubes enhances their overall structural integrity, enabling them to withstand hydrodynamic forces such as wave and coastal currents. After five months, a height reduction of approximately 0.4 meters was observed, likely due to settlement of the sludge filling. Monitoring conducted 2 years after installation indicated that the sludge fill remained solid and well-consolidated with no sign of damage, thereby confirming good performance of the structure. Satellite imagery analysis 40 months post installation indicated shoreline accretion accompanied by a significant expansion of mangrove growth, reaching up to 50 m beyond the initial vegetation line. These findings suggest that sludge-filled GI-Tubes can be an effective, low-cost, and sustainable solution for mitigating coastal erosion in soft-soil coastal environments.